Malaysia’s new code of ethics for journalists: a critical review - Davie, William R (Penerbit Universiti Kebangsaan Malaysia, 2024)
Codes of conduct for journalists often serve as an ethical guide for best practices beyond necessary laws aimed at punishing harm to reputation, privacy, and public decency. While such codes may be viewed as preventative measures to stave off official mechanisms of enforcement, there are instances where the independence of journalists is abrogated by government oversight. The Malaysian Press Institute adopted a national manual of journalism ethics in 1989; then 35 years later the Malaysian government reviewed it, revised it, and adopted eight new standards. Malaysia’s communication ministry announced the new code in 2024 to fight against the spread of offensive and fake news accounts while ensuring integrity and professionalism among the nation’s journalists. This study is a critical review based on comparative antecedents and contemporary review of the tenets of the new code of conduct. The Malaysia Media Council was established in 2018 as an institution for updating media rules for print, broadcast, and online media. This study also explains the administrative factors leading up to the code of conduct’s implementation including the controversial mechanism declared for its enforcement. The eight standards were established not only as a means of ensuring ethical conduct in newsgathering and dissemination but also as a way for challenging the government’s grant of press certification. Ultimately, an argument is made based on the importance of independence as central to the ethical principles of professional journalism.